Integrated Management and Biocontrol of Vegetable and Grain Crops Nematodes - Ciancio, A.; Mukerji, K. G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
The second volume of the IMPD series describes aspects related to most important phytoparasitic nematodes, considering the integration of biological control methods with other management practices and technologies, including the use of predatory nematodes and microbial rhizosphere antagonists. Chapters cover topics like the mode of action and interactions of nematophagous fungi, the efficacy of controll and management of plant parasitic nematode communities through a soil conservation approach, and exploitation of nematodes-bacteria antagonistic relationships. A focus is given on regional issues, like the management of nematodes parasitizing staple crops, i.e. andean tubers or some important grain crops, like soybean in North and South America or cereals. A review on nematode management in cotton is integrated by a chapter on management of nematodes on wheat. New technologies are also revised, including the potentials of control methods based on RNA interference and issues related to the use of biofumigation to control nematodes in different regional or crop contexts.
Nematodes in Biological Control -- Biological Control Potentials Of Predatory Nematodes -- Integration of Biological Control with other Methods of Nematode Management -- Mode of Action and Interactions of Nematophagous Fungi -- Crops Ecology and Control -- Control and Management of Plant Parasitic Nematode Communities in a Soil Conservation Approach -- Management of Nematodes of Andean Tuber and Grain Crops -- Ipm of Soybean Cyst Nematode in The Usa -- The Soybean Cyst Nematode Heterodera Glycines Ichinohe, 1952 in Argentina -- Nematode Management in Cotton -- Technological Advances in Sustainable Management -- The Potential of Rna Interference for the Management of Phytoparasitic Nematodes -- Potential Use of Pasteuria Spp. In The Management of Plant Parasitic Nematodes -- Sustainable Methods For Management Of Cyst Nematodes -- Biofumigation To Manage Plant-Parasitic Nematodes -- Data Analysis and Knowledge-based Applications -- Global Knowledge And Its Application For The Integrated Control And Management Of Nematodes On Wheat -- Integrated Management Of Root-Knot Nematodes In Mediterranean Horticultural Crops -- Modeling Nematodes Regulation By Bacterial Endoparasites.
Keywords: LIFE SCIENCES; AGRICULTURE; ECOLOGY; BOTANY; PLANT DISEASES; INVERTEBRATES; LIFE SCIENCES; PLANT PATHOLOGY; INVERTEBRATES; PLANT SCIENCES; AGRICULTURE; ECOLOGY